Cost-Effectiveness and Cost-Utility Analysis of the Treatment of Emotional Disorders in Primary Care: PsicAP Clinical Trial. Description of the Sub-study Design - Ruiz-Rodríguez, Paloma; Cano-Vindel, Antonio; Muñoz-Navarro, Roger; Wood, Cristina M.; Medrano, Leonardo A.; Moretti, Luciana Sofía; , PsicAP Research Group (Frontiers in Psychology, 2018)
Introduction: In the primary care (PC) setting in Spain, the prevalence of emotional disorders (EDs) such as anxiety, depression and somatoform disorder is high. In PC patients, these disorders are not always managed in accordance with the recommendations provided by clinical practice guidelines, resulting in major direct and indirect economic costs and suboptimal treatment outcomes. The aim is to analyze and compare the cost-effectiveness and cost-utility of group-based psychological therapy versus treatment as usual (TAU). Methods: Multicentre, randomized controlled trial involving 300 patients recruited from PC centres in Madrid, Spain, with symptoms or possible diagnosis of anxiety, mood (mild or moderate), or somatoform disorders. Patients will be randomized to one of two groups: an experimental group, which will receive group-based transdiagnostic cognitive-behavioral therapy (TD-CBT); and a control group, which will receive TAU (mainly pharmacological interventions) prescribed by their general practitioner (GP). Clinical assessment will be performed with the Patient Health Questionnaire (PHQ). Direct and indirect costs will be calculated and relevant socio-demographic variables will be registered. The Spanish version of the EuroQol 5D-5L will be administered. Patients will be assessed at baseline, immediately after treatment finalization, and at 6 and 12 months post-treatment. Discussion: To our knowledge, this is the first study to compare TD-CBT to TAU in the PC setting in Spain. This is the first comparative economic evaluation of these two treatment approaches in PC. The strength of the study is that it is a multicentre, randomized, controlled trial of psychotherapy and TAU for EDs in PC. Trial registration: Protocol code: ISCRCTN58437086; 20/05/2013 EUDRACT: 2013-001955-11. Protocol Version: 6, 11/01/2014.